Przemiany w sektorze przetwórstwa żywca wieprzowego na Podkarpaciu w latach 1999-2005 - Stec, Artur; Ruda, Maria (Changes in Pork Processing Sector in the Podkarpackie Province in the Years 1999-2005, 2006)
In the period preceding Poland's accession to the European Union, porkers processing plants had been expected to adapt to the EU standards by introducing i.e. food safety systems (HACCP) and pork carcass classification (EUROP). However, not all of the plants satisfied the requirements concerning introduction of costly procedures and necessary modernization of buildings and equipment. As a result, from 1999 to 2005 there was a decrease of 23% in quantity of meat processing plants in the Podkarpackie Voivodeship.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 614-620